Recombinant LH supplementation improves cumulative live birth rates in the GnRH antagonist protocol: a multicenter retrospective study using a propensity score-matching analysis - Meng Wang; Rui Huang; Xiaoyan Liang; Yundong Mao; Wenhao Shi; Qian Li (BMC, 2022)
Abstract Background Luteinizing hormone (LH) is critical in follicle growth and oocyte maturation. However, the value of recombinant LH (r-LH) supplementation to recombinant follicle stimulating hormone (r-FSH) during controlled ovarian stimulation in the gonadotrophin releasing hormone (GnRH) antagonist regimen is controversial. Methods This multicenter retrospective cohort study recruited 899 GnRH antagonist cycles stimulated with r-LH and r-FSH in 3 reproductive centers and matched them to 2652 r-FSH stimulating cycles using propensity score matching (PSM) for potential confounders in a 1:3 ratio. The primary outcome was the cumulative live birth rate (CLBR) per complete cycle. Results The baseline characteristics were comparable in the r-FSH/r-LH and r-FSH groups after PSM. The r-FSH/r-LH group achieved a higher CLBR than the r-FSH group (66.95% vs. 61.16%, p = 0.006). R-LH supplementation also resulted in a higher 2-pronuclear embryo rate, usable embryo rate, and live birth rate in both fresh embryo transfer cycles and frozen-thawed embryo transfer (FET) cycles. No significant differences were found in the rate of moderate and severe ovarian hyperstimulation syndrome (OHSS), or cycle cancellation rate in the prevention of OHSS. Conclusions R-LH supplementation to r-FSH in the GnRH antagonist protocol was significantly associated with a higher CLBR and live birth rate in fresh and FET cycles, and improved embryo quality without increasing the OHSS rate and cycle cancellation rate.